Ist die EU-Agrarpolitik ihr Geld wert? - Dieter Kirschke; Ulrich Koester; Astrid Häger (Wirtschaftsdienst, 2014)
Der Erfolg einer Politik wird häufig mit dem Umfang der eingesetzten Finanzmittel gleichgesetzt. Die Autoren dieses Beitrag halten eine solche Einschätzung für verfehlt. Vielmehr sollten die Kosten dem Nutzen gegenübergestellt und einzelne Instrumente nicht mit unterschiedlichen Zielen überfrachtet werden. Die EU-Agrarpolitik der letzten Dekaden liefert Beispiele für Fehleinschätzungen des Politikerfolgs. – – Expenditure for the Common Agricultural Policy (CAP) has been in the centre of recent policy debate in the preparation of the Financial Framework for the period 2014-2020. Expenditure has generally been considered as the necessary costs for the achievement of the CAP objectives. The authors of this article argue that expenditure is not equal to the economic costs of a policy. Moreover, they claim that the main part of CAP expenditure is not well targeted for the achievement of the CAP's objectives. The bulk of expenditure is for direct payments tied to agricultural land and, hence, contributes little if anything to CAP's objectives as laid down in the treaties of the European Union or offi cially articulated elsewhere.
Keywords: F1; H4; Q1; 330; EU-Agrarpolitik; Wirkungsanalyse; EU-Staaten